104k views
5 votes
Enter the values for the highlighted variables that show how to subtract the rational expressions correctly:

a =

b =

c =

d =

e =

f =

g =

1 Answer

6 votes

Answer:

a = 6

x^2 + 6x is equal to x(x+6)

b=2

Denominator and numerator of the first term are multiplied by x.

c=6

Second term is multiplied by (x-6)/(x-6)

d=2

Now that they have the same denominator, the two terms are combined. 2 is the coefficient of the first term

e=6

In the same way as d is carried over from b, e is carried over from c.

f = 6

2x - x + 6 = x + 6

g = 1

We factor out the (x+6) from the numerator and denominator

User JoGoFo
by
6.0k points